1989
DOI: 10.1111/j.1600-0536.1989.tb04747.x
|View full text |Cite
|
Sign up to set email alerts
|

Heracleum mantegazzianum growth phases and furocoumarin content

Abstract: The observation of photocontact dermatitis from Heracleum mantegazzianum Sommier et Levier in 2 gardeners at work prompted the analysis of furocoumarin content of stem, leaves and fruits of the plant during a period of 1 year. Their concentration was found to be maximal in fruit, intermediate in leaf, and minimal in stem. Psoralen was the most prevalent substance in the leaf and bergapten in the fruit. In the stem, in contrast, individual furocoumarins were found in lower but variable concentrations. 3 furocou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…We attempted to find the reason for such an abundant occurrence of the compound on the leaves of H. Sosnowskyi. Other authors found the greatest amount of furanocoumarin during the flowering period in two Heracleum species (Pira et al 1989;Zobel and Brown 1990b).…”
Section: R a F Tmentioning
confidence: 85%
“…We attempted to find the reason for such an abundant occurrence of the compound on the leaves of H. Sosnowskyi. Other authors found the greatest amount of furanocoumarin during the flowering period in two Heracleum species (Pira et al 1989;Zobel and Brown 1990b).…”
Section: R a F Tmentioning
confidence: 85%
“…Mü llerová et al 2005;Nielsen et al 2005) and occurs as both open stands and dense (dominant) stands in a range of different habitats (Tiley et al 1996;Thiele and Otte 2006). Owing to its phototoxic compounds (furanocumarins: Pira et al 1989) and its potential negative effects on local phytodiversity, H. mantegazzianum belongs to a group of the most important invasive plants species in Germany and is one of a few adventitious plant species outside crop fields that are selectively managed (Schepker and Kowarik 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Both Knudsen (1983) using material from Denmark and Pira et al (1989) using material from Italy found maximum levels in the fruit, with intermediate levels in the leaves, followed by the roots, and the lowest levels in the stem. Psoralen was the predominant furanocoumarin in the leaves and bergapten in the fruit (Pira et al 1989). Furanocoumarin levels peaked in spring and early summer and declined in late summer and autumn.…”
Section: Historymentioning
confidence: 99%
“…It is well known that H. mantegazzianum causes phytophotodermatitis, a serious skin inflammation resulting from the activation, under ultraviolet radiation, of compounds contained in the plant sap (Kuske 1940;Drever and Hunter 1970;Camm et al 1976a). The major phytotoxic principles in Heracleum species are linear furanocoumarins or psoralens, mainly 5-methoxypsoralen and 8-methoxypsoralen (Pathak et al 1967;Nielsen 1970;Molho et al 1971;Pira et al 1989). Toxicity is due to cross-linking of the furan ring with pyrimidine bases (thymine) of DNA in the presence of ultraviolet light at 315-400 nm.…”
Section: Economic Importance and Environmentalmentioning
confidence: 99%